Glass photochromic heat insulation film as well as preparation method and application thereof
By optimizing the acidification and hydrothermal reaction conditions of the hydrothermal method, an efficient tungsten trioxide nano powder was prepared, which solved the problem of low photochromic efficiency and achieved efficient ultraviolet and infrared shielding and thermal insulation properties of the thermal insulation film.
Patent Information
- Application Number
- CN202510008788.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
Tungsten trioxide has low photochromic efficiency, limiting its further development and application in thermal insulation materials.
By optimizing the acidification and hydrothermal reaction conditions of the hydrothermal method, the acidification is carried out using a mixed acid solution of oxalic acid and hydrochloric acid, and the hydrothermal reaction process of staged heating is used to prepare tungsten trioxide nanopowder with high light absorption and photochromic properties.
The photochromic efficiency of tungsten trioxide is improved, and the prepared heat insulation film has good ultraviolet and infrared shielding and thermal insulation properties.
Smart Images

Figure CN119797432A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photochromic materials, and in particular relates to a glass photochromic thermal insulation film and a preparation method and application thereof. Background Art
[0002] Photochromism refers to a compound A that undergoes a specific chemical reaction when exposed to light of a certain wavelength to obtain another product B. Due to the change in structure, its absorption spectrum changes significantly, but it can return to its original form under the irradiation of light of another wavelength or the action of heat. Photochromism is a reversible chemical change. Compounds that can undergo reversible color changes under the action of light are called photochromic compounds or photochromics.
[0003] Tungsten trioxide is a photochromic material that can be used in automotive glass, architectural glass and other fields in the form of thermal insulation film, thereby reducing energy consumption and improving human comfort. Tungsten trioxide film can show color through light radiation of appropriate energy. When tungsten trioxide film is irradiated by light, electrons e - and hole h + The photogenerated electrons enter the conduction band of tungsten trioxide, and the photogenerated holes react with the adsorbed water on the surface of the film to generate H + , and then diffuses into the interior of tungsten trioxide, causing the color to change.
[0004] The research of photochromic materials has become a hot topic in materials science. As an important inorganic photochromic material, tungsten trioxide has the advantages of good stability and is widely used in the research of photochromic materials. However, the photochromic efficiency of tungsten trioxide is low, which limits its further development and application. Therefore, improving the photochromic and thermal insulation properties of WO3 has important guiding significance for the development and research of thermal insulation materials. Summary of the invention
[0005] In order to improve the photochromic efficiency of tungsten trioxide, the first purpose of the present invention is to provide a method for preparing tungsten trioxide nanopowder, the second purpose is to provide tungsten trioxide nanopowder prepared by the above preparation method, the third purpose is to provide the application of the above tungsten trioxide nanopowder in the preparation of glass photochromic thermal insulation film, and the fourth purpose is to provide a method for preparing glass photochromic thermal insulation film. The tungsten oxide nano sample prepared by the method of the present invention has good light absorption rate and photochromic performance, and the prepared thermal insulation film has the characteristics of shielding ultraviolet rays and infrared rays and heat insulation, and has good comprehensive performance.
[0006] In order to achieve the above object, the specific scheme adopted by the present invention is:
[0007] In a first aspect, a method for preparing tungsten trioxide nanopowder comprises the following steps: Step 1: prepare a sodium tungstate aqueous solution, and add a mixed acid solution to the sodium tungstate aqueous solution while stirring; the mixed acid solution is obtained by mixing hydrochloric acid and oxalic acid with a concentration of 3.0 mol / L in a volume ratio of 6:1-3; then continue stirring for 1-1.5 hours in a dark environment to obtain a precursor solution; Step 2: Move the precursor solution into a stainless steel reactor lined with polytetrafluoroethylene, react at 160-170°C for 15-18h, then cool to 100-120°C and continue to react for 3-5h. After cooling to room temperature, centrifuge and sediment to obtain a yellow powder precipitate. Wash the yellow powder precipitate with alcohol and water for multiple times, dry it at 60-80°C for 4-5h, and grind it to obtain a tungsten trioxide sample powder.
[0008] Preferably, the concentration of the sodium tungstate aqueous solution is 0.1-0.5 g / mL. Furthermore, the volume ratio of the mixed acid solution to the sodium tungstate aqueous solution is 4-5:30-40.
[0009] Preferably, in step 2, the reaction conditions in the stainless steel reactor are: react at 170° C. for 15 h, then cool to 110° C. and continue reacting for 5 h.
[0010] In the second aspect, tungsten trioxide nanopowder is prepared by the above preparation method.
[0011] The third aspect is the application of the above-mentioned tungsten trioxide nanopowder in the preparation of glass photochromic thermal insulation film.
[0012] In a fourth aspect, a method for preparing a glass photochromic thermal insulation film comprises the following steps: Step 1: According to the mass percentage, 30% tungsten trioxide powder, 35% additive and 35% diluent are mixed and ground for 48 hours to obtain a mixed nano slurry; Step 2: According to the mass percentage, 30% of the nano pulp, 50% of the acrylic acid aminic glue and 20% of the diluent are mixed and stirred for half an hour to obtain a glue solution; Step 3: Mix 50% glue and 50% diluent by volume, stir for half an hour, apply on PET film, and then dry and compound; Step 4: Mix the UV varnish and the diluent, apply them on the other side of the PET film, dry them, and cure them with a UV lamp to obtain a glass photochromic thermal insulation film.
[0013] Preferably, the auxiliary agent includes at least one of a dispersant, a leveling agent, a defoaming agent and a thickener.
[0014] Preferably, the diluent is water and / or alcohol.
[0015] Beneficial effects: The present invention conducts in-depth research on the preparation of tungsten trioxide nanopowders, explores effective ways to improve photochromic properties, and optimizes the hydrothermal method. Starting from the acidification and hydrothermal reaction conditions, it is found that the addition of oxalic acid during the acidification process has a significant effect on the photochromic properties of the prepared thermal insulation film, and that too much or too little oxalic acid added in a ratio with hydrochloric acid will lead to a decrease in color change properties. In addition, the present invention adopts staged heating during the hydrothermal reaction process, first reacting at 160-170°C for 15-18h, then cooling to 100-120°C and continuing to react for 3-5h, exploring the optimal conditions for improving photochromic properties, which has important scientific significance for promoting the industrial application of tungsten trioxide materials, and also has guiding significance for the development of thermal insulation materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a comparison chart of the color difference values of the photochromic thermal insulation films prepared in each group. DETAILED DESCRIPTION
[0017] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0018] Unless otherwise specified, the reagents described in the present invention are all conventional commercially available reagents, and the operating methods used are all conventional technical methods.
[0019] Example 1
[0020] Prepare a 0.1g / mL sodium tungstate aqueous solution, and add 4mL of mixed acid solution to 30mL of the sodium tungstate aqueous solution while stirring. The mixed acid solution is obtained by mixing hydrochloric acid and oxalic acid with a concentration of 3.0mol / L in a volume ratio of 6:1. Then continue stirring for 1.5h in the dark to obtain a precursor solution.
[0021] The precursor solution was transferred into a stainless steel reactor lined with polytetrafluoroethylene, reacted at 160°C for 18 hours, then cooled to 100°C and continued to react for 3 hours. After cooling to room temperature, it was centrifuged to obtain a yellow powder precipitate. The yellow powder precipitate was washed with alcohol and water for multiple times, dried at 80°C for 5 hours, and ground to obtain a tungsten trioxide sample powder.
[0022] Example 2
[0023] Prepare 0.1g / mL sodium tungstate aqueous solution, add 4mL mixed acid solution to 30mL of the sodium tungstate aqueous solution, and stir while dripping. The mixed acid solution is obtained by mixing hydrochloric acid and oxalic acid with a concentration of 3.0mol / L in a volume ratio of 6:3. Then continue stirring for 1.5h in the dark to obtain a precursor solution.
[0024] The precursor solution was transferred into a stainless steel reactor with a polytetrafluoroethylene liner, reacted at 170°C for 15 hours, then cooled to 110°C and continued to react for 5 hours. After cooling to room temperature, it was centrifuged to obtain a yellow powder precipitate. The yellow powder precipitate was washed with alcohol and water for multiple times, dried at 80°C for 5 hours, and ground to obtain a tungsten trioxide sample powder.
[0025] Example 3
[0026] Prepare a 0.1g / mL sodium tungstate aqueous solution, and add 4mL of mixed acid solution to 30mL of the sodium tungstate aqueous solution while stirring. The mixed acid solution is obtained by mixing hydrochloric acid and oxalic acid with a concentration of 3.0mol / L in a volume ratio of 6:2. Then continue stirring for 1h in the dark to obtain a precursor solution.
[0027] The precursor solution was transferred into a stainless steel reactor with a polytetrafluoroethylene liner, reacted at 165°C for 16 hours, then cooled to 120°C for a further 4 hours, cooled to room temperature, and centrifuged to obtain a yellow powder precipitate. The yellow powder precipitate was washed with alcohol and water for multiple times, dried at 80°C for 5 hours, and ground to obtain a tungsten trioxide sample powder.
[0028] The tungsten trioxide sample powder prepared in Example 1-3 was analyzed: Phase analysis: X-ray diffractometer was used to observe the crystal structure of the sample powder. It was found that the sample powder had good crystallinity and was a monoclinic tungsten trioxide powder. No impurities appeared in the spectrum. Phase analysis: SEM test of the obtained sample powder showed that the sample showed a relatively uniform pure phase, which was monoclinic WO3.
[0029] Comparative Example 1
[0030] Prepare a 0.1g / mL sodium tungstate aqueous solution, add 4mL of 3.0mol / L hydrochloric acid to 30mL of the sodium tungstate aqueous solution, and stir while dropping. Then, continue stirring for 1h in the dark to obtain a precursor solution.
[0031] The precursor solution was transferred into a stainless steel reactor with a polytetrafluoroethylene liner, reacted at 165°C for 16 hours, then cooled to 120°C for a further 4 hours, cooled to room temperature, and centrifuged to obtain a yellow powder precipitate. The yellow powder precipitate was washed with alcohol and water for multiple times, dried at 80°C for 5 hours, and ground to obtain a tungsten trioxide sample powder.
[0032] This control example is substantially the same as Example 1, except that only 4 mL of 3.0 mol / L hydrochloric acid was used for acidification.
[0033] Comparative Example 2
[0034] Prepare a 0.1g / mL sodium tungstate aqueous solution, add 4mL of 3.0mol / L hydrochloric acid to 30mL of the sodium tungstate aqueous solution, stirring while dropping, and then continue stirring for 1h in the dark to obtain a precursor solution.
[0035] The precursor solution was transferred into a stainless steel reactor lined with polytetrafluoroethylene, reacted at 160°C for 18 hours, cooled to room temperature, and centrifuged to obtain a yellow powder precipitate. The yellow powder precipitate was washed with alcohol and water for multiple times, dried at 80°C for 5 hours, and ground to obtain a tungsten trioxide sample powder.
[0036] This control example is basically the same as Example 1, except that: during the acidification process, 4 mL of 3.0 mol / L hydrochloric acid is used; and during the hydrothermal reaction process, the reaction is only carried out at 160° C. for 18 h.
[0037] Comparative Example 3
[0038] This control example is basically the same as Example 1, except that during the hydrothermal reaction, the reaction was carried out at 200° C. for 20 h.
[0039] Comparative Example 4
[0040] Prepare a 0.1g / mL sodium tungstate aqueous solution, and add 4mL of mixed acid solution to 30mL of the sodium tungstate aqueous solution while stirring. The mixed acid solution is obtained by mixing hydrochloric acid and oxalic acid with a concentration of 3.0mol / L in a volume ratio of 6:1. Then continue stirring for 1.5h in the dark to obtain a precursor solution.
[0041] The precursor solution was transferred into a stainless steel reactor lined with polytetrafluoroethylene, reacted at 100°C for 3h, then heated to 160°C and continued to react for 18h. After cooling to room temperature, it was centrifuged to obtain a yellow powder precipitate. The yellow powder precipitate was washed with alcohol and water for multiple times, dried at 80°C for 5h, and ground to obtain a tungsten trioxide sample powder.
[0042] This control example is basically the same as Example 1, except that during the hydrothermal reaction, the reaction was first performed at 100° C. for 3 h, and then the temperature was raised to 160° C. and the reaction was continued for 18 h.
[0043] Comparative Example 5
[0044] The control example is substantially the same as Example 1, except that the mixed acid solution is obtained by mixing hydrochloric acid and oxalic acid, both of which have a concentration of 3.0 mol / L, in a volume ratio of 6:4.
[0045] The tungsten trioxide sample powder prepared in Examples 1-3 and Comparative Examples 1-4 was used to prepare a thin film, and the preparation steps were as follows: Step 1: According to the mass ratio, 30% tungsten trioxide powder, 35% additive and 35% diluent are mixed and ground for 48 hours to obtain a mixed nano slurry; Step 2: According to the mass ratio, 30% tungsten trioxide nano-slurry, 50% acrylic acid acrylonitrile and 20% diluent are stirred for half an hour to obtain glue solution; Step 3: Mix 50% glue and 50% diluent by volume, stir for half an hour, and apply. The glue passes through the coating equipment and is applied to the PET film for drying and compounding. Step 4: Apply UV varnish + thinner to the PET film on the other side, dry it, and use a UV lamp to cure it to prevent scratches.
[0046] In the above steps, ethanol is used as the diluent, and ethylene glycol monobutyl ester is used as the auxiliary agent, which is conducive to film formation.
[0047] According to conservative tests, the above thermal insulation film has a 20% infrared blocking rate and 80% light transmittance; if under ultraviolet excitation (sunlight exposure): 99% blocking rate and 15% light transmittance.
[0048] Figure 1 The color difference comparison chart of the photochromic thermal insulation films prepared in each group is shown. As can be seen from the figure, the film prepared by using the tungsten trioxide powder described in Examples 1-3 has a relatively large color difference value, which indicates that the concentration of conduction electrons in the nanocrystals in the film is high, which is conducive to the generation of photogenerated electrons and holes, so the color difference value is large, the band gap is narrow, the electrons are easily excited to the conduction band, and the photochromic performance is strong.
[0049] By comparing Example 1 with Control Example 1, it can be seen that when oxalic acid is not added during the acidification process, the color difference value is significantly reduced. This may be because the addition of oxalic acid changes the crystal structure, reduces its structural integrity, increases defect states, and is conducive to the transmission of protons. Furthermore, compared with Control Example 5, it can be seen that the amount of oxalic acid added is very critical. If the amount of oxalic acid added is too little, it is not easy to cause defect states. If the amount of oxalic acid added is too much, the local periodic lattice will be destroyed, so that the electron holes cannot be effectively separated, and the color difference value is reduced. The results show that the volume ratio of 6:1-3 between hydrochloric acid and oxalic acid is most suitable.
[0050] During the hydrothermal reaction, the present application adopts staged heating, first reacting at 160-170°C for 15-18h, and then cooling to 100-120°C for 3-5h. By comparing the various embodiments and control examples, it can be seen that the hydrothermal reaction conditions are also a key factor affecting the photochromic properties of tungsten trioxide. As shown in Control Example 3, the powder prepared by reacting at 200°C for 20h can also cause photochromism of the thermal insulation film, but the performance is not as good as Examples 1-3. This may be because different temperature reaction conditions will lead to changes in the size or morphology of the grains. When the grains become larger and the specific surface area decreases, it is not conducive to the absorption and utilization of light energy in the photochromic process.
[0051] It should be noted that the above-described embodiments should be understood as illustrative rather than limiting the scope of protection of the present invention, and the scope of protection of the present invention shall be subject to the claims. For those skilled in the art, some non-essential improvements and adjustments made to the present invention still fall within the scope of protection of the present invention without departing from the essence and scope of the present invention.
Claims
1. A method for preparing tungsten trioxide nanopowder, characterized in that: The following steps are involved: Step 1: prepare a sodium tungstate aqueous solution, and add a mixed acid solution to the sodium tungstate aqueous solution while stirring; the mixed acid solution is obtained by mixing hydrochloric acid and oxalic acid with a concentration of 3.0 mol / L in a volume ratio of 6:1-3; then continue stirring for 1-1.5 hours in a dark environment to obtain a precursor solution; Step 2: Move the precursor solution into a stainless steel reactor lined with polytetrafluoroethylene, react at 160-170°C for 15-18h, then cool to 100-120°C and continue to react for 3-5h. After cooling to room temperature, centrifuge and sediment to obtain a yellow powder precipitate. Wash the yellow powder precipitate with alcohol and water for multiple times, dry it at 60-80°C for 4-5h, and grind it to obtain a tungsten trioxide sample powder.
2. The preparation method according to claim 1, characterized in that: The concentration of the sodium tungstate aqueous solution is 0.1-0.5 g / mL.
3. The preparation method according to claim 2, characterized in that: The volume ratio of the mixed acid solution to the sodium tungstate aqueous solution is 4-5:30-40.
4. The preparation method according to claim 1, characterized in that: In step 2, the reaction conditions in the stainless steel reactor are: 170° C. for 15 h, then cooled to 110° C. and continued to react for 5 h.
5. Tungsten trioxide nanopowder prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the tungsten trioxide nanopowder according to claim 5 in preparing a glass photochromic thermal insulation film.
7. A method for preparing a glass photochromic thermal insulation film, characterized in that: The following steps are involved: Step 1: According to the mass percentage, 30% tungsten trioxide powder, 35% additive and 35% diluent are mixed and ground for 48 hours to obtain a mixed nano slurry; the tungsten trioxide powder is the tungsten trioxide nano powder as claimed in claim 5; Step 2: According to the mass percentage, 30% of the nano pulp, 50% of the acrylic acid aminic glue and 20% of the diluent are mixed and stirred for half an hour to obtain a glue solution; Step 3: Mix 50% glue and 50% diluent by volume, stir for half an hour, apply on PET film, and then dry and compound; Step 4: Mix the UV varnish and the diluent, apply them on the other side of the PET film, dry them, and cure them with a UV lamp to obtain a glass photochromic thermal insulation film.
8. The preparation method according to claim 7, characterized in that: The auxiliary agent includes at least one of a dispersant, a leveling agent, a defoamer and a thickener.
9. The preparation method according to claim 7, characterized in that: The diluent is water and / or alcohol.